CReSCENT: CanceR Single Cell ExpressioN Toolkit. Issue Volume 48:Issue W1(2020) (1st June 2020) - Mohanraj, Suluxan; Díaz-Mejía, J Javier; Pham, Martin D; Elrick, Hillary; Husić, Mia; Rashid, Shaikh; Luo, Ping; Bal, Prabnur; Lu, Kevin; Patel, Samarth; Mahalanabis, Alaina; Naidas, Alaine; et al.
Abstract: CReSCENT: CanceR Single Cell ExpressioN Toolkit (https://crescent.cloud ), is an intuitive and scalable web portal incorporating a containerized pipeline execution engine for standardized analysis of single-cell RNA sequencing (scRNA-seq) data. While scRNA-seq data for tumour specimens are readily generated, subsequent analysis requires high-performance computing infrastructure and user expertise to build analysis pipelines and tailor interpretation for cancer biology. CReSCENT uses public data sets and preconfigured pipelines that are accessible to computational biology non-experts and are user-editable to allow optimization, comparison, and reanalysis for specific experiments. Users can also upload their own scRNA-seq data for analysis and results can be kept private or shared with other users.